Aplicação de modelos de sequências quase periódicas em guias de onda ópticos - Bezerra Segundo, Marcos Tulio Antunes (2023)
One of the most traditional segmentation models applied in optical waveguides is the Bragg Grating, also known as Fiber Bragg Grating (FBG), where the sequencing in the propagation region follows a periodic pattern. More recently, some models of quasiperiodic sequences have been applied in photonic crystals, especially considering devices with onedimensional stratifi cation. In this work, waveguides based on directing light through media with refractive index sequenced in the propagation direction are proposed. The core guiding model of these structures is based on quasiperiodic sequencing of the refractive index that forms the signal propagation region. In this context, wellknown optical fiber models are modified to fit the segmentation structures of the signalguiding regions. Core fracturing structures of waveguide models were investigated by applying quasiperiodic models such as Fibonacci, Thue Morse, Double Period, and Octonacci sequences with the aim of comparing their performance with guides using Bragg Grating as a segmentation strategy. For this study, COMSOL® software was used to simulate various types of segmentation. Transmission and reflection parameters at the interfaces between the different media making up the applied sequences were analyzed. The results obtained show similarities between the transmission response of the proposed guides and quasiphotonic crys tals they were based on, but with the addition of absorptance, a phenomenon not previously observed. Another factor observed in the results was the applicability of these segmented waveguides as thermal sensors, even showing better responses than their periodic counterparts.